A Structural View on Medicinal Chemistry Strategies against Drug Resistance. Issue 11 (14th January 2019) - Agnello, Stefano; Brand, Michael; Chellat, Mathieu F.; Gazzola, Silvia; Riedl, Rainer
Abstract: The natural phenomenon of drug resistance is a widespread issue that hampers the performance of drugs in many major clinical indications. Antibacterial and antifungal drugs are affected, as well as compounds for the treatment of cancer, viral infections, or parasitic diseases. Despite the very diverse set of biological targets and organisms involved in the development of drug resistance, the underlying molecular mechanisms have been identified to understand the emergence of resistance and to overcome this detrimental process. Detailed structural information on the root causes for drug resistance is nowadays frequently available, so next‐generation drugs can be designed that are anticipated to suffer less from resistance. This knowledge‐based approach is essential for fighting the inevitable occurrence of drug resistance. Abstract : Resistance is futile : The emergence of drug resistance has far‐reaching consequences for clinical efficacy. This Review presents an analysis of the underlying structural mechanisms of drug resistance across different therapeutic indications and highlights rational approaches to overcome this threat to public health.